2020
DOI: 10.1002/mar.21398
|View full text |Cite
|
Sign up to set email alerts
|

Turning the other cheek: Facial orientation influences both model attractiveness and product evaluation

Abstract: The layout of visual elements in advertising influences consumers' perception and judgments. The research reported here investigates the influence of the face orientation of a human model on the perception of their attractiveness and its downstream consequences on product evaluation. Across five experiments, we first demonstrate that consumers tend to perceive a model's face showing his or her left cheek as more attractive than when showing the right cheek, even when the images are otherwise identical. More im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 79 publications
0
9
0
Order By: Relevance
“…Corresponding rightward head-turning biases, revealing one's left cheek to others, were found when participants posed for a portrait in an emotional context, in photography composition [180][181][182][183], when rating mirrored portraits [184], and, with clear preference for right-facing objects rather than left-facing ones [183,185]. Recently, Park, Spense, Ishii, and Togawa (2020) [116] reported that left-oriented faces were perceived as more attractive than right-oriented faces, even when stimuli were identical. The authors found the perceived prototypicality as the mediator but a closer inspection may identify in the brain's asymmetric frequency tuning the mechanism underlying apparently dissociable phenomena related to left-oriented faces: more fixations [186], ease of recognition [187], prototypicality, and attractiveness [116].…”
Section: Aestheticsmentioning
confidence: 90%
See 2 more Smart Citations
“…Corresponding rightward head-turning biases, revealing one's left cheek to others, were found when participants posed for a portrait in an emotional context, in photography composition [180][181][182][183], when rating mirrored portraits [184], and, with clear preference for right-facing objects rather than left-facing ones [183,185]. Recently, Park, Spense, Ishii, and Togawa (2020) [116] reported that left-oriented faces were perceived as more attractive than right-oriented faces, even when stimuli were identical. The authors found the perceived prototypicality as the mediator but a closer inspection may identify in the brain's asymmetric frequency tuning the mechanism underlying apparently dissociable phenomena related to left-oriented faces: more fixations [186], ease of recognition [187], prototypicality, and attractiveness [116].…”
Section: Aestheticsmentioning
confidence: 90%
“…The painting 'Vertumnus' by Guiseppe Arcimboldo of Panel E is filtered from https://commons.wikimedia.org/wiki/File:Vertumnus_årstidernas_gud_målad_av_Giuseppe_ Arcimboldo_1591_-_Skoklosters_slott_-_91503.tiff; public domain. The model's photo of Panel F is filtered and adapted from Figure 1 of Reference [116], licensed under the Copyright Clearance Center. The anatomy of visual pathways is redrawn after Figure 1 of Reference [117], licensed under CC-BY, version 4.0.…”
Section: Brain's Asymmetric Frequency Tuning (Baft) As Generalized Acmentioning
confidence: 99%
See 1 more Smart Citation
“…Processing information can elicit a sense of fluency that depends on the level of difficulty experienced in the mental process (Park et al, 2021). The processing of an external visual stimulus is considered to be fluent when it is cognitively easy or instantaneous.…”
Section: Processing Fluencymentioning
confidence: 99%
“…There are already several scientific studies showing how the use of automated facial analysis of expressions provides positive results in assessing CX (de Wijk et al, 2012;He et al, 2012;Terzis et al, 2013;Danner et al, 2014;El Haj et al, 2017;Noordewier and van Dijk, 2019;Riem and Karreman, 2019;Meng et al, 2020). Recently, new pioneering studies presented by the scientific literature have shown the possibility to take advantage of face orientation aside from facial expression to predict the hedonic impact of the face presentation of models, as the facial orientation to the right-side significantly predicts with a more negative evaluation, while on the opposite, face orientation towards left side significantly correlates with a positive evaluation of the models' face presentation (Park et al, 2021). Facial expressions reveal affective states defined, for instance, in EMFACS-7 (Friesen and Ekman, 1978) and thus possibly predict related behaviour and attitude modification (Kulczynski et al, 2016).…”
Section: Related Research Workmentioning
confidence: 99%